1995
DOI: 10.1016/0014-5793(95)00312-w
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of human plasminogen activators and plasminogen

Abstract: Plasminogen (PC), urokinase-type plasminogen activator (u-PA) and tissue-type PA (t-PA) are the main molecules involved in fibrinolysis and in many other physiological and pathological processes. In the present study we report that human t-PA, purified from human melanoma cells, and PG, purified from human plasma, both contain P-Tyr residues, as revealed by immunoblotting analyses with monoclonal anti-P-Tyr antibodies. In addition HPLC amino acid analysis of acid-hydrolyzed t-PA, PG and u-PA, shows that: (i) P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…However, the pI of Pg 2ε is more acidic [24], suggesting an additional secondary modification of its structure which may be critical for its capacity to induce the expression of MMP-9. This shift in the pI of Pg 2ε may be associated with phosphorylation of the Pg molecule [63]. In this context, a shift in the pI of u-PA from 9.2 to 7.6, secondary to the phosphorylation of Tyr and Ser residues, is associated with the activation of pp60 src and of protein kinase C in metastatic tumour cells [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pI of Pg 2ε is more acidic [24], suggesting an additional secondary modification of its structure which may be critical for its capacity to induce the expression of MMP-9. This shift in the pI of Pg 2ε may be associated with phosphorylation of the Pg molecule [63]. In this context, a shift in the pI of u-PA from 9.2 to 7.6, secondary to the phosphorylation of Tyr and Ser residues, is associated with the activation of pp60 src and of protein kinase C in metastatic tumour cells [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Several studies have aimed to elucidate plasminogen structure-function relationships and interactions with other molecules, but the only PTMs described are N-and O-linked glycosylations and a phosphorylation in Ser 578. 43,44 The functional relevance of the new p-sites described here has yet to be elucidated, but they could influence plasminogen activation or plasmin enzymatic activity as it occurs with the urokinase-type plasminogen activator 45 or other enzymes involved in the coagulation cascade 46 which are regulated by phosphorylation processes. Other identified phosphoproteins related with the complement and coagulation cascades include the complement components 3 and 8, the complement factor I, the coagulation factor V, fibrinogen alpha, alpha-2 macroglobulin, kininogen, the mannan-binding lectin serine peptidase 1 and the serpins antithrombim-III, alpha-2-antiplasmin and heparin cofactor 2 ( Figure 4).…”
Section: Carrascal Et Almentioning
confidence: 98%
“…Receptor-bound urokinase is phosphorylated on tyrosine and serine residues in a human metastatic carcinomatous cell line (26). Others have shown that urokinase from human urine and from HT1080 fibrosarcoma cells contains phosphotyrosine residues, although no functional effects have been reported as yet (27,28). Recent data from this laboratory indicate that two phosphorylation sites are located within the A and B chains of pro-uPA (Ser 138/303 ) from A431 human carcinoma cells and that pro-uPA phosphorylation renders the protease unable to activate uPAR-dependent signaling in myeloid cells (29).…”
Section: /mentioning
confidence: 99%